Driving Impairment Cases Involving Etizolam and Flubromazolam. Issue 1 (13th May 2020) - Rohrig, Timothy P; Osawa, Kei A; Baird, Tyson R; Youso, Kimberly B
Abstract: This study describes 12 cases of drivers stopped for impaired driving, where a designer benzodiazepine was detected, specifically etizolam or flubromazolam. Etizolam was detected in three cases, with blood concentrations ranging from 40 to 330 ng/mL. Two of these cases had low concentrations of methamphetamine and/or amphetamine, and in the third case tetrahydrocannabinol (THC) was detected. Flubromazolam was detected in nine cases; in all cases, at least one other drug was detected, with THC being the most prevalent. The mean blood concentration of flubromazolam was 16.3 ng/mL and had a median concentration of 17.0 ng/mL, ranging from 7.0 to 31 ng/mL. The low concentrations of designer benzodiazepines that produce pharmacological effects may allow many of these drugs to go undetected using routine testing in laboratories; therefore, it is necessary to include these novel compounds within validated analytical methods to reduce the chance of reporting false negative results. The prevalence in which laboratories are detecting the presence of novel benzodiazepines in impaired drivers illustrates the increased threat to public safety. These case studies demonstrate the importance of investigating agencies and forensic laboratories to be vigilant in monitoring the emerging novel psychoactive substances in their region.